Outbreak of novel coronavirus (2019-nCoV): The first three-month experience of anesthesiologists in Thai university hospital - Kiatkasemsan, Benjamas; Chaichalothorn, Mutita; Payongsri, Titipon; Charuluxananan, Somrat (Chulalongkorn Medical Journal, 2020)
The pandemic of the new coronavirus disease, COVID-19, has involved in 750,890 cases worldwide with 36,405 (4.8%) deaths as of 31st March 2020. The virus is novel to human and there is no vaccine yet. Thailand was the first country after China that reported a confirmed COVID-19 patient on 13th January 2020. At the end of March, total confirmed COVID-19 cases in Thailand were 1,524 cases with 9 deaths (0.6%). Emerging Infectious Disease Health Science Centre, Faculty of Medicine, Chulalongkorn University was able to detect novel coronavirus on 8th January 2020 before it was confirmed by matching its genome with China’s laboratory. King Chulalongkorn Memorial Hospital, the Thai Red Cross Society, was well prepared for COVID-19 patients. Laboratory capacity for detection was increased. An isolated building was specifically arranged for isolation and providing cares to COVID-19 patients. Anesthesiologists are at high risk of infection because of exposure to droplets and aerosols during airway procedures. Preparation of equipment such as video-laryngoscopes, medications and appropriate personal protective equipment were completed before the admission of the first COVID-19 patient. As being anesthesiologists in a Thai university hospital, on call staffs were consulted for endotracheal intubation in 8 critically ill patients during 18 - 31 March 2020 (14 days). In summary, anesthesiologists in Thai university hospital were consulted for endotracheal intubation in the early phase of the epidemic and would have a major role for perioperative care for patients in the progression of outbreak in Thailand.